China's urban champions the politics of spatial development - Jaros, Kyle A. (Princeton studies in contemporary China., 2019)
The rise of major metropolises across China since the 1990s has been a double-edged sword: although big cities function as economic powerhouses, concentrated urban growth can worsen regional inequalities, governance challenges, and social tensions. Wary of these dangers, China's national leaders have tried to forestall top-heavy urbanization. However, urban and regional development policies at the subnational level have not always followed suit. China's Urban Champions explores the development paths of different provinces and asks why policymakers in many cases favor big cities in a way that reinforces spatial inequalities rather than reducing them.Kyle Jaros combines in-depth case studies of Hunan, Jiangxi, Shaanxi, and Jiangsu provinces with quantitative analysis to shed light on the political drivers of uneven development. Drawing on numerous Chinese-language written sources, including government documents and media reports, as well as a wealth of field interviews with officials, policy experts, urban planners, academics, and businesspeople, Jaros shows how provincial development strategies are shaped by both the horizontal relations of competition among different provinces and the vertical relations among different tiers of government. Metropolitan-oriented development strategies advance when lagging economic performance leads provincial leaders to fixate on boosting regional competitiveness, and when provincial governments have the political strength to impose their policy priorities over the objections of other actors.Rethinking the politics of spatial policy in an era of booming growth, China's Urban Champions highlights the key role of provincial units in determining the nation's metropolitan and regional development trajectory.